Protective effects of shikimic acid against thioacetamide-induced hepatic fibrosis: role of Nrf2/NF-κB signaling pathways - Albrakati, Ashraf (Frontiers in Pharmacology, 2025)
BackgroundLiver fibrosis is a chronic condition marked by scar tissue accumulation in the liver that impairs function. Shikimic acid (SA) has demonstrated significant antioxidant and anti-inflammatory properties and is a hydroaromatic natural product found in various plant sources, including star anise. Thioacetamide (TAA) is commonly used as an experimental model to induce liver fibrosis. This study was designed to investigate the protective effects of SA against TAA-induced liver fibrosis in rats.MethodsFifty male Wistar rats were divided into five groups (n = 10): control, TAA (200 mg/kg), SA (50 mg/kg), and two combination groups receiving TAA plus SA (50 and 100 mg/kg). Treatments were administered intraperitoneally for 6 weeks. Liver function, oxidative stress markers, inflammatory mediators, apoptotic proteins, fibrogenic factors, and histopathology were assessed.ResultsSA treatment significantly attenuated liver fibrosis induced by TAA through improved liver enzymes, including alkaline phosphatase (ALP) and aspartate transaminase (AST), serum alanine transaminase (ALT) and antioxidant parameters, including catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), and superoxide dismutase (SOD). SA-enhanced nuclear factor erythroid 2-related factor-2 (Nrf2) expression while reducing oxidative stress markers, including nitric oxide (NO), malondialdehyde (MDA) and reduced glutathione (GSH), and inflammatory mediators, including tumour necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β) and nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-κB). Furthermore, SA demonstrated anti-apoptotic effects by modulating Bax, Bcl2, and caspase-3 levels and exhibited anti-fibrotic properties through suppression of transforming growth factor beta (TGF-β) and collagen type I alpha-1 chain (COL1A1) expressions. Notably, SA improved histopathological alterations with a slight presence of fibroplasia. These protective effects were more pronounced at the higher dose (100 mg/kg).ConclusionSA effectively protected against TAA-induced liver fibrosis through multiple mechanisms, including the normalisation of liver enzymes, enhancement of antioxidant defences via Nrf2 activation, suppression of inflammatory mediators, and modulation of apoptotic and fibrogenic pathways.